PERAN MEDIA AUDIO VISUAL BERBASIS ETNOSAINS UNTUK MENINGKATKAN MINAT BELAJAR SISWA KELAS IV UPT SPF SD INPRES PERUMNAS ANTANG III - Goin, Etti Selpiana; Fitriana HS, Eka; Satriawati, Satriawati; Alam, Syamsul (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2025)
This study aims to improve students' learning interest by using Audio-Visual Media Based on Ethnoscience for fourth-grade students at SD Inpres Perumnas Antang III. The approach used is a quantitative approach with a classroom action research design. Data collection techniques include observation and documentation, following a sequence of planning, implementation, observation, and reflection. The subjects of this research were 22 third-grade students of UPT SPF SD Inpres Perumnas Antang III. The results showed that teacher activity observations in Cycle I scored 2.0, categorized as fair, and in Cycle II increased to 2.8, categorized as good. Meanwhile, student activity observations in Cycle I scored 2.0 (fair category) and in Cycle II improved to 3.5 (good category). Students’ learning interest in Cycle I was in the fair category, while in Cycle II, it reached the good category. It can thus be concluded that there was an improvement in students’ learning interest after using ethnoscience-based audio-visual media.